Best Answer

There's no answer to be found, because the expression doesn't ask any question,

such as "What is the value of 'x' ?".

The expression can be cleaned up a bit, by combining like terms. Then it can be written as

5x + 52

but it hasn't changed. It's still just an expression, its value depends on the value of 'x',

and 'x' can be any number at all.

Again, there's no answer, because there's no question.

Q: What is the answer to 32x - 27x plus 52?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x2 + 27x = 30 ∴ x2 + 9x - 10 = 0 ∴ (x + 10)(x - 1) = 0 ∴ x ∈ {-10, 1}

4x^2 + 32x + 64 = 4(x^2 + 8x + 16) = 4(x + 4)^2 = 4(x + 4)(x + 4)

64

Note that 16X is a factor of 32X [16X times 2 is 32X]. So now whether it's (32X)^4 or 32 times (X^4), that will still be the LCM, so the answer is 32X to the 4th power, just as it's stated in the question.

15x + 32x - 28 = 47x - 28 = (√47x)2 - (√28)2 = (√47x)2 - (2√7)2 = (√47x - 2√7)(√47x + 2√7)

Related questions

It is: 23-27x when simplified

3x2 + 27x +60

4x + 32x + 9 = 36x + 9

5X + 2 = 32X - 1subtract 5X from both sides:2 = 27X -1add 1 to both sides:3 = 27Xdivide both sides by 27:3/27 = XorX = 3/27, which reduces to 1/9therefore,x=1/9

32x + 8 – 34x

0.9 sq m

If 32X + 53 = 501, then 32X = 448, and X = 448/32 = 14.

35x + 10

That's pretty easy. Just add the like terms (2x and 32x) and keep the 3. You get 34x plus 3.

9 + 9y = 27x -9 -9 9y = 27x - 9 9y/9 = 27x/9 - 9/9 y = 3x -1

Isolating xx = (6+6)/32x = 0.375

-16x2 + x + 8 = -1/64(32x - 1 - √513)(32x - 1 + √513)